Relationship Between Skin Shame, Psychological Distress and Quality of Life in Patients with Psoriasis: a Pilot Study - Donja Homayoon; Michaela Hiebler-Ragger; Moritz Zenker; Wolfgang Weger; Human Unterrainer; Elisabeth Aberer (Medical Journals Sweden, 2020)
Shame has been registered as a part of psychosocial distress in patients with psoriasis. This study investigated 44 patients with psoriasis and 88 age- and sex-matched individuals without skin disease. Skin shame, multifarious expressions of shame, psychological symptoms, overall health, dermatological quality of life, disease burden and disease severity were measured. Higher levels of skin shame correlated with a greater disease burden (r=0.63; p < 0.01), higher Dermatology Life Quality Index (r=0.33; p < 0.05), and lower mental quality of life (r=-0.30; p < 0.05). Patients had a higher level of skin shame (F=74.03; eta2= 0.36; p < 0.01) and less physical quality of life on the SF-36 (F=5.14; eta2= 0.04; p < 0.05) than non-dermatological controls. General shame was not related to disease burden or quality of life. While self-rated skin shame appears to be related to quality of life in patients with psoriasis, no association was registered between expert-rated Psoriasis Area and Severity Index and quality of life.